The implementation of the theoretical humanism paradigm in holistic education - Primarni, Amie; Masuwd, Mowafg; Makmudi, Makmudi; Fa’atin, Salmah; Nuhdi, Asep (Univeritas Papua, 2025)
This article examines the implementation of the theoretical humanism paradigm in holistic education, an approach that integrates human values and divine values. The research question asked is why it uses the paradigm of theoretical humanism to be implemented in holistic education. This research aims to explore the theory, philosophical foundation, and application of holistic education based on theocentric humanism. With the library research method, the results of the study show that the implementation of this paradigm includes the formulation of a curriculum based on divine values, moral reinforcement through reflective practices, the development of spirituality-based critical thinking skills, and the formation of a school culture that supports spiritual and intellectual harmony. This paradigm is also in line with the values of the Qur'an and hadith, which emphasizes morality and belief in the formation of a whole character. The conclusion suggests that this approach provides a solid foundation philosophically and provides practical implications in preparing students for worldly challenges while achieving greater spiritual closeness. This article is expected to contribute to the development of a curriculum based on divine and human values in the context of Islamic education to answer the challenges of modern education.